2010
DOI: 10.1021/la104031b
|View full text |Cite
|
Sign up to set email alerts
|

Direct Observation by Laser Scanning Confocal Microscopy of Microstructure and Phase Migration of PVC Gels in an Applied Electric Field

Abstract: The fluorescent probe lucigenin was incorporated in poly(vinyl chloride) (PVC) gels, and laser scanning confocal microscopy (LSCM) was used to clarify the internal structures of the gels. From the two-dimensional and three-dimensional information by LSCM, we first observed the internal structure of the PVC gel at a wet status, where the PVC gels comprised a polymer-rich phase and a polymer-poor phase uniformly with a three-dimensional network structure. After an electric field was applied, an effect of the ele… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
18
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 31 publications
(18 citation statements)
references
References 22 publications
0
18
0
Order By: Relevance
“…Plasticized PVC gels have also shown excellent flexibility, ability to conform to irregular surfaces and have a high surface tension 16 . Additionally, PVC gels have many advantages as actuators such as their ability to move in air, large strains, high output stresses, high response rates, and stability under thermal influence 17 . It has been theorized that deformation in PVC gels is caused by electric charge injection at the cathode, plasticizer migration, and the Maxwell force caused by the electric field between two parallel electrodes 18 .…”
Section: Introductionmentioning
confidence: 99%
“…Plasticized PVC gels have also shown excellent flexibility, ability to conform to irregular surfaces and have a high surface tension 16 . Additionally, PVC gels have many advantages as actuators such as their ability to move in air, large strains, high output stresses, high response rates, and stability under thermal influence 17 . It has been theorized that deformation in PVC gels is caused by electric charge injection at the cathode, plasticizer migration, and the Maxwell force caused by the electric field between two parallel electrodes 18 .…”
Section: Introductionmentioning
confidence: 99%
“…This will reduce the molecular crystallinity and the film becomes more uniform and softer. When DBA is added, the polymer network swells and forms a gel structure with polymer‐rich and polymer‐poor phases, as shown in Figure (c). The area with minute particles is the polymer‐rich phase, and the area with linear structures is the polymer‐poor phase.…”
Section: Resultsmentioning
confidence: 99%
“…[8] Moreover,3 Di mages can be reconstructed by collecting images at different depths along the Z-axis. [9] The development of confocal fluorescence microscopy provides great opportunities for visualizationi nm aterial science.…”
Section: Introductionmentioning
confidence: 99%
“…It has been reported that the resolution limits of 200–300 nm in the lateral direction and 500–700 nm in the axial direction can be obtained for confocal fluorescence microscopy . Moreover, 3D images can be reconstructed by collecting images at different depths along the Z ‐axis . The development of confocal fluorescence microscopy provides great opportunities for visualization in material science.…”
Section: Introductionmentioning
confidence: 99%